STUDI EVALUATIF SISTEM PEMBELAJARAN BAHASA ARAB DI MA PUTRA PONDOK MODERN DARUSSALAM LIABUKU KOTA BAU BAU - Talim, Ahmad (Inspiratif Pendidikan, 2020)
The focus of this research is the Arabic learning system in MA Putra Bau Bau Darussalam Islamic Boarding School in Bau Bau City. From these problems, this study aims to evaluate the Arabic learning system in Darussalam Islamic Boarding School which is focused on the main issues, namely: 1) How is the compatibility of the Antasedent Arabic learning system entry in Darussalam Liabuku Bau Bau Islamic boarding school with the process standard?This type of research is a program evaluation with a descriptive qualitative approach, in this study the authors assess the quality level and conditions of the Arabic language learning system in Darussalam Islamic Boarding School Liabuku Bau Bau. To obtain the data, three data collection techniques were used, namely observation, interviews and documentation. After data collection, the data processing is then processed through three stages, namely: 1) data reduction, 2) data display, 3) and drawing conclusions / verification.The results of this study indicate that learning Arabic in MA Putra Darussalam Liabuku Islamic boarding school is fulfilled with 3 standard processes, namely: achieving the existing Arabic learning objectives, teachers in MA Kulliyatul Muallimin al-Islamiyah Darussalam Liabuku Islamic boarding school Bau Bau make I 'dad al-Tadrīs to support the existing Arabic teaching and learning activities, because all of his learning uses Arabic as the medium. In evaluating students 'theoretical or practical language skills, the teacher evaluates learning in the form of oral examinations (imtihᾶn syafahi) and written examinations (imtihᾶn tahrīrī), so that the assessment of students' Arabic Arabic abilities cannot be separated in the four language skills.From this research, a strategic recommendation can be adopted in improving the learning system of KMI Pondok Modern Darussalam Liabuku, namely teachers working with Language Builders in language programs to improve the ability of the Santri Arabic language and provide a Language Laboratory to improve students' listening skills.